Impact in the Academic Environment on Online Learning and Student Achievement During The Covid-19 Pandemic - Rosmawati (CV ODIS, 2022)
At this time the world of education is experiencing many challenges as a result of the Covid-19 pandemic, therefore the government has issued a policy of learning from home using online methods to suppress the spread of the virus. This pandemic will change the learning environment that requires adaptation and has an impact on all students. The influence of the learning environment on learning motivation will also have an impact on academic achievement. The purpose of this study was to determine the effect of learning motivation on academic achievement in students undergoing online learning during the covid-19 pandemic. This research is a type of quantitative research using a cross-sectional design. The sample used in this study amounted to 85 respondents, with a simple random sampling method used as a sampling technique in the population. The data was distributed to respondents using a questionnaire distributed via google form to facilitate access during the pandemic period, the data analysis used is the Spearman test. The correlation test results showed that there was no significant effect between learning motivation and academic achievement of students undergoing online learning during the covid-19 pandemic, with p=0.288. Achievement in this academic field cannot be influenced by motivation alone, but there are several supporting factors as well as the background. So efforts are needed to improve the quality of learning during the Covid-19 pandemic